2016
DOI: 10.1097/bot.0000000000000612
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic-Induced Cardiovascular Complications During Reamer–Irrigator–Aspirator-Assisted Femoral Nonunion Treatment

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Thirteen studies [ 18 , 42 , 43 , 45 , 47 , 48 , 50 , 55 60 ] reported blood loss in a total number of 336 performed procedures with the RIA system. Of these 13 studies, five studies [ 47 , 48 , 50 , 56 , 58 ] reported the volume of blood lost, which resulted in a mean of 803.29 ml per case.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen studies [ 18 , 42 , 43 , 45 , 47 , 48 , 50 , 55 60 ] reported blood loss in a total number of 336 performed procedures with the RIA system. Of these 13 studies, five studies [ 47 , 48 , 50 , 56 , 58 ] reported the volume of blood lost, which resulted in a mean of 803.29 ml per case.…”
Section: Resultsmentioning
confidence: 99%
“…However, application of the RIA system can also cause serious complications. The RIA system is considered an one-time aggressive reamer with continuous irrigation at the reamer head that can cause eccentric reaming and blood loss, causing iatrogenic fractures and cardiopulmonary disturbances, respectively [ 17 , 18 ]. However, precisely these features of powerful evacuation on medullary canal content furthered the application of the RIA device as a multipurpose tool to lower the risk of dissemination into the soft tissues and systemic circulation as well as clearing the femoral/tibial canal of cement debris.…”
Section: Introductionmentioning
confidence: 99%
“…These case reports found that each cardiac event happened toward the end of the RIA procedure, possibly resulting from underestimated blood loss with high volumes of irrigation fluid used. 18 Dawson et al found that operative time and amount of graft harvested differed significantly between RIA and ICBG. On average, the patients undergoing graft harvest with RIA had less operative time, less pain, and greater volume of graft harvested, 12 but healing rate and time to healing did not vary significantly.…”
Section: Discussionmentioning
confidence: 99%
“…These case reports found that each cardiac event happened toward the end of the RIA procedure, possibly resulting from underestimated blood loss with high volumes of irrigation fluid used. 18…”
Section: Discussionmentioning
confidence: 99%
“…Although RIA has achieved very promising results with respect to cavity defects, this technique is less useful for segmental ones, for which osteosynthesis supplementation is required. Furthermore, complications can arise in relation to the learning curve, to over-reaming and, in some patients, to cardiac problems produced by rapid blood loss; the latter complication is closely related to previous cardiopathy[ 22 , 23 ].…”
Section: Reamer-irrigator-aspiratormentioning
confidence: 99%